Agricultural zoning of climate risk for Physalis peruviana cultivation in Southeastern Brazil - Oliveira Aparecido, Lucas Eduardo de; Batista, Rafael Madureira; Silva Cabral de Moraes, Jose Reinaldo da [UNESP]; Silva Costa, Cicero Teixeira; Moraes-Oliveira, Adriana Ferreira de [UNESP] (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to elaborate the agricultural zoning of climatic risk (ZARC) for Physalis peruviana, through the thermal and water requirements of the crop in Southeastern Brazil. Air temperature (T-AIR) and precipitation (P-YEAR) data from 1,530 meteorological stations covering the entire region were used. Regions were considered climatically favorable to Physalis peruviana when T-AIR was between 13 and 18 degrees C and P-YEAR between 1,000 and 2,000 mm per year. Regions where T-AIR was above 30 degrees C or less than 13 degrees C were considered inapt. Maps were created with this information and used to identify climatic characteristics and to establish the agricultural aptitude classes, termed apt, inapt, and marginal for the cultivation of Physalis peruviana. The Southeastern region of Brazil showed a thermal variation from 16.5 to 22.6 degrees C and water amplitude from 800 to 2,800 mm. ZARC shows that 10% of Southeastern Brazil is climatically apt for the cultivation of Physalis peruviana, corresponding to the following regions of Brazilian states: central and southern Minas Gerais, western Rio de Janeiro and Espirito Santo, and eastern and southern Sao Paulo.
Keywords: climate risk; agrometeorology; modeling; big data